Effect of Work Environment and Leadership on Employee Performance through Work Motivation during the Covid-19 Pandemic - Prawira Aditya Rahman; Zainal Arifin; Iqbal Firdausi; Safril Safril; Kevin Cherly Tanujaya (AIBPM Publisher, 2022)
This study aims to analyze (1) the effect of the work environment on employee performance, (2) the effect of leadership on employee performance, (3) the effect of work motivation on employee performance, (4) the effect of the work environment on work motivation, (5) the effect of leadership on employee performance. work motivation, (6) the effect of the work environment on employee performance motivation through work motivation, and (7) the effect of leadership on employee performance through work motivation.The research population is the employees of Balai Konservasi Sumber Daya alam Kalimantan Selatan. Samples were taken from as many as 91 people who were selected randomly through proportional random sampling. The data were analyzed using PLS-SEM (Partial Least Square-Structural Equation Modeling) analysis through the SmartPLS version 3.0 program.The results of the study show that: (1) the work environment has no effect on employee performance, (2) leadership has an effect on employee performance, (3) work motivation has an effect on employee performance, (4) work environment has an effect on work motivation, (5) leadership has an effect on on work motivation, (6) work environment affects employee performance through work motivation, (7) leadership affects employee performance through work motivation.Â Keywords: Work Environment, Leadership, Work Motivation, Employee Performance